The effectiveness of sociodrama techniques in preventing moral disengagement tendencies in high school students - Aisy, Rihadatul; Prihatiningsih, Riskiyana; Rahman, Diniy Hidayatur (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2024)
The increasing behavior of students who violate morals can reflect the increasing tendency of students' moral disengagement. Sociodrama is believed to be an effective technique in preventing moral disengagement tendencies in students. This research aims to prove the effectiveness of sociodrama techniques in preventing the tendency of moral disengagement in students. This research design uses a one group pretest-posttest design. The research sample was 25 students from class XI-2 of Kepanjen Islamic High School, obtained through purposive sampling. The instrument used to collect data is the moral disengagement scale. Data analysis was carried out using the Wilcoxon Signed-Rank Test. The results of the Wilcoxon Signed-Rank Test show that sociodrama techniques are effective in preventing the tendency of moral disengagement in students. The novelty in this research lies in the classical guidance service with sociodrama techniques which functions as a preventive service that focuses on students with a moderate level of moral disengagement. Meanwhile, previous research used different techniques and functioned as a curative service that focused on students with a high level of moral disengagement. This research concludes that sociodrama techniques are effective in preventing the tendency of moral disengagement in high school students. The implications of these findings show the importance of applying sociodrama techniques in guidance and counseling programs in schools.